Talimogene Laherparepvec in Advanced Mucosal Melanoma of the Urethra Upon Primary Resistance on Immune Checkpoint Inhibition: A Case Report - Fröhlich, Anne; Hoffmann, Friederike; Niebel, Dennis; Egger, Eva; Kukuk, Guido M.; Toma, Marieta; Sirokay, Judith; Bieber, Thomas; Landsberg, Jennifer (Frontiers in Oncology, 2020)
Background: Mucosal melanomas including melanomas of the urogenital tract represent a rare type of melanoma characterized by low mutational burden and poor prognosis. Immune checkpoint inhibition has so far only been assessed in a limited number of mucosal melanoma patients and, in contrast to response in cutaneous melanoma, was associated with disappointing response rates. The oncolytic viral immunotherapy Talimogene laherparepvec (T-VEC) has recently been approved for treatment of locally advanced or unresectable melanoma. T-VEC combines direct oncolytic effects with local and systemic immune-mediated anti-tumor response. Our rationale to use T-VEC in this case was an expected augmentation of immunogenicity by tumor lysis to overcome primary resistance of a mucosal melanoma to immune checkpoint blockade. Objective: To report the first case of an advanced mucosal melanoma of the urethra treated with intralesional application of Talimogene laherparepvec. Case Report: A 78-years old female patient was diagnosed with an advanced mucosal melanoma of the urethra with inguinal lymph node metastases and intravaginal mucosal metastases. Shortly after surgical resection of the tumor mass, intravaginal mucosal metastases, and new nodal metastases in proximity of the left iliac vessels were diagnosed. The patient was treated with the anti-PD1 antibody pembrolizumab and obtained a stable disease lasting for 30 weeks. However, upon checkpoint inhibition the patient developed a loco-regional progressive disease featuring bleeding intravaginal metastases, while nodal metastases remained stable. We stopped treatment with pembrolizumab and administered T-VEC directly into the intravaginal mucosal metastases. After five injections T-VEC yielded a partial response with clinical regression of the injected mucosal metastases. Disease remained stable for 16 weeks under biweekly T-VEC treatment. Thereafter the patient showed disease progression in nodal metastases. T-VEC was discontinued. Immunotherapy with pembrolizumab was restarted but failed to achieve a response. Finally, targeted therapy with imatinib was induced in presence of a druggable c-KIT mutation, leading to a considerable response of all tumor sites that is still ongoing. Conclusion: T-VEC represents an effective and well-tolerated treatment option for patients with loco-regionally advanced mucosal melanoma. In combination with immunotherapy, T-VEC bears the potential of synergistic effects to overcome the specific primary resistance of mucosal melanoma to immune checkpoint blockade.